칼만 필터를 이용한 2축 회전형 관성항법장치의 초기위치 보정 정박 중 정렬 알고리즘 설계 - 류경돈; Kyung-don Ryu (한국항행학회논문지, 2024)
관성항법장치는 정지 상태에서 가속도계 및 자이로 센서가 측정한 중력과 지구 자전 각속도 정보를 이용하여 정렬을 수행하며, 일반적으로 선형 항법 오차 모델 기반의 영속도 보정 칼만필터를 사용하여 수행된다. 하지만 이는 정지 상태를 가정하여 설계된 알고리즘으로 해상 정박 중 정렬을 수행하는 경우, 파도로 인해 발생하는 움직임으로 정렬 오차가 커지거나 필터가 발산하게 된다. 본 논문에서는 큰 방위각 오차 모델과 초기위치 보정 기법을 사용하여 해상 플랫폼을 위한 정박 중 정렬 알고리즘을 설계하고 시뮬레이션을 통해 검증하였다. 또한 이를 회전형 관성항법장치에 적용하였을 경우 바이어스가 상쇄되는 원리를 통해 비약적으로 성능이 개선됨을 확인하였다. INS(inertial navigation system) aligns itself using gravity and Earth’s rotational rate from accelerometers and gyro sensors when stationary. Typically, ZUPT(zero velocity update), which is based on a linear error model Kalman filter, is used when it is stationary. However, such algorithms assume stationary conditions, leading to increased alignment errors or filter divergence during maritime mooring due to wave-induced motion. This paper designs a mooring alignment algorithm for maritime platforms using a Kalman filter, which uses large heading angle error model and an initial position correction technique. And it is validated by simulation. Furthermore, it is confirmed that applying this to a rotational INS dramatically improves performance through the principle of bias cancellation.